2018
DOI: 10.1007/s10592-018-1129-9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of adaptive potential and functional diversity: integrating old and new approaches

Abstract: Continuing advances in whole genome scale approaches integrated with other 'omic' technologies promise to revolutionise understanding about the relevance of genetic variation to risks of species declines and extinctions. In the face of the vastly increased accessibility of such approaches, it is important that we advance beyond descriptive genetics to developing a more functional perspective on whether enhancing genetic variation is the most effective strategy for conservation management. Rather than a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 157 publications
(163 reference statements)
1
85
0
Order By: Relevance
“…Another presentation reviewed the importance and potential for measuring both adaptive and deleterious variation in threatened populations (see Freedman et al 2016). In the special issue Mable (2019) acknowledges the importance of genomic methods towards the conservation of adaptive potential, but suggests that integration with ecological methods and concepts remains essential. She stresses the importance of work towards understanding adaptive processes, beyond merely descriptive data.…”
Section: The Meeting and Discussionmentioning
confidence: 99%
“…Another presentation reviewed the importance and potential for measuring both adaptive and deleterious variation in threatened populations (see Freedman et al 2016). In the special issue Mable (2019) acknowledges the importance of genomic methods towards the conservation of adaptive potential, but suggests that integration with ecological methods and concepts remains essential. She stresses the importance of work towards understanding adaptive processes, beyond merely descriptive data.…”
Section: The Meeting and Discussionmentioning
confidence: 99%
“…It should be noted here that the LWfG as a species has one of the highest levels of genetic diversity among birds 39 , 40 . Nonetheless, the comparatively lower diversity in the Swedish population signifies a reduced potential to adapt to changes in the environment 41 . Also, the increased amount of inbreeding in the Swedish population, and in particular the excess of long RoHs observed in our analyses, suggest that the Swedish population has been subject to recent mating between close relatives 42 , 43 , which may be explained by a generally small population size and/or significant influence from the captive breeding programme.…”
Section: Discussionmentioning
confidence: 99%
“…The IUCN definition of a species is provided online: ‘A group of interbreeding individuals with common characteristics that produce fertile (capable of reproducing) offspring and which are not able to interbreed with other such groups, that is, a population that is reproductively isolated from others’ (https://www.iucn.org/downloads/en_iucn_glossary_definitions.pdf), which is essentially the BSC. Given discrepancies in defining ‘species’, some scientists have suggested that conservation biology would benefit the most by concentrating on assessing the adaptive potential of evolutionary significant units rather than engage in mental gymnastics about ‘species’ (Fraser & Bernatchez, 2001; Funk, McKay, Hohenlohe, & Allendorf, 2012; Mable, 2019; Stanton et al., 2019).…”
Section: Species Subspecies and Endangered Speciesmentioning
confidence: 99%